Dynamical Behavior of a Stochastic Nutrient-Plankton Food Chain Model with Lévy Jumps (Journal of Nonlinear Modeling and Analysis, 2024)
In aquatic ecosystem, plankton populations are easily affected byenvironmental fluctuations due to the unpredictability of many physical factors. To better understand how environmental fluctuations influence planktonpopulations, in this paper, we propose and investigate a stochastic nutrient-plankton food chain model with Lévy jumps. Firstly, by constructing a suitableLyapunov function, we prove that the stochastic model has a unique globalpositive solution for any given positive initial value. Then, we establish sufficient conditions for the persistence and extinction of plankton. Finally, weprovide some numerical simulations to illustrate the analytical results.